PENGEMBANGAN BAHAN AJAR IPS BERBASIS PENINGGALAN SEJARAH LOKAL PADA MATERI PENINGGALAN SEJARAH - Wina Yanti Nasution; Hidaya Hidaya; Yusnadi Yusnadi (JURNAL TEMATIK, 2019)
This study aims to produce social studies based social studies teaching materials on historical relic materials. This type of research is development research with the Dick & Carey development model. The results showed that: (1) the learning outcomes obtained by the experimental class were higher than the learning outcomes obtained by the control class. This was seen in the results of the pre test and post test conducted by researchers. At the time of the pre-test of 31 students in class IV-A only 13 people (41.94%) completed, while another 18 people (58.06%) did not complete with RRK 60. While in class IV-B out of 34 students only 10 people (29.41%) who finished, as many as 24 more people (70.59%) had not finished with RRK 56.03. At the time of the post-test of class IV-A as many as 28 students (90.32%) had completed only 3 more people (9.68%) who did not complete with RRK 68.71. While from class IV-B as many as 33 people (97.06%) had been completed, the remaining 1 person (2.94%) who had not completed the RRK was 73.82. (2) The validity of the product also gets a very good value, it is proven from the values obtained from the four validators, namely: material validation score 3.62 (90.63%), language validation score 3.75 (93.75%), the media validation score was 3.69 (92.19%), and the learning design validation score was 4.00 (100%).